Identification of descriptor for CO desorption in CO2 electrochemical reduction on single-atom catalyst - Peng, Xinyue (Nanyang Technological University, 2024)
The continuous utilization of fossil fuels leads to serious emissions of anthropogenic greenhouse gases, primarily carbon dioxide (CO2), which significantly contributes to political instability due to its impact on climate change. Consequently, the urgent need to reduce atmospheric CO2 levels has become apparent. Recent research has focused on directly converting CO2 into carbon monoxide (CO) through CO2 electrochemical reduction (CO2RR) using electrocatalysts. However, these electrocatalysts are not yet effective enough, as they face challenges. Due to the inherent stability of CO2, a high overpotential is required for initiation, which poses problems for the activity and stability of the catalyst. Under the same conditions, the hydrogen evolution reaction (HER) is also initiated, leading to reduced selectivity of the catalyst and a lower CO yield. CO2RR also encounters issues with a low conversion rate, largely dependent on CO desorption process rate. Therefore, there is an urgent demand to develop an ideal electrocatalyst for CO2RR with high activity, selectivity, and efficiency. To achieve this, identifying the descriptor that is closely related to its performance is necessary, as it plays a significant role in guiding the rational catalyst design. In this project, Single-Atom Catalysts (SACs) with the M-N4-C structure was utilized to investigate descriptors for CO2RR, as this type of catalyst has shown the potential to enhance the reaction. The metallic central atoms of the electrocatalysts were replaced with ten common metals. With the application of Density Functional Theory (DFT) calculations, the reaction pathway was simulated and used to compare and analyse their performance in terms of activity and selectivity. Additionally, Density of States (DOS) and Crystal Orbital Hamilton Population (COHP) methods were employed to observe the change in d-orbitals of each catalyst during the desorption process, aiming to identify a descriptor strongly correlated with the desorption rate. Through observation and analysis, it has been determined that Co-M4-N possesses significant potential for utilization as a catalyst in CO2RR. Moreover, maintaining a certain distance between the metallic atom and the absorbate CO ensured both effective adhesion and a high desorption rate. By examining the π-back donation of the transition metal in the catalyst and the ligand CO, a descriptor exhibiting a strong correlation with the catalyst's desorption rate was identified.